Mental health in people with substance use disorder: differential aspects between men and women - Santos de Pacual, Asunción; Saura Garre, Pedro; López Soler, Concepción (Anales de Psicología / Annals of Psychology, 2020)
The aim of this study is to present the psychopathological profile and the differences between men and women who start an addition residential treatment. The sample included 142 patients (116 were men and 26 women). We analysed socio-demographic variables, consumption pattern as well as personality disorders and clinical syndromes using EuropASI and MCMI-III as evaluating instruments. Men group showed a high prevalence at antisocial personality disorder (31%). On the other hand, women did so at depressive (23,1%), dependent (26,9%) and antisocial (26,9%) patterns, finding statistically significant differences only at the dependent disorder. At clinical syndromes men showed a relevant prevalence when analysing substances dependence (86,2%), anxiety disorder (60,3%) and alcohol dependence (45,7%), and women group at anxiety disorder (76,9%), alcohol dependence (69,2%), substances (53,8%) and dysthymic (46,2%). We found statistically significant differences at anxiety disorder, dystymic and alcohol dependence where women appeared to be more affected. At thought clinical syndrome men raised higher scores, and women did so at depression, being both differences statistically significant. The results are discussed and their clinical implications analysed. Keywords: dual diagnosis, personality disorders, addiction, psychopathology, gender.